Eco-Innovation in Industry. Enabling green growth (Paris, 2011)
"Eco-innovation will be a key driver of industry efforts to tackle climate change and realise "green growth" in the post-Kyoto era. Eco-innovation calls for faster introduction of breakthrough technologies and for more systemic application of available solutions, including non-technological ones. It also offers opportunities to involve new players, develop new industries and increase competitiveness. Structural change in economies will be imperative in coming decades.